Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-74911-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Reduce Consequences of Radiation Exposure

Abstract: Antioxidants have been studied for their capacity to reduce the cytotoxic effects of radiation in normal tissues for at least 50 years. Early research identified sulfur-containing antioxidants as those with the most beneficial therapeutic ratio, even though these compounds have substantial toxicity when given in-vivo. Other antioxidant molecules (small molecules and enzymatic) have been studied for their capacity to prevent radiation toxicity both with regard to reduction of radiation-related cytotoxicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 62 publications
1
55
0
2
Order By: Relevance
“…Several studies have shown that overexpression of Prx I increases cellular resistance to oxidative stress (25)(26)(27). Radiation sensitivity might rely on the cells' ability to manage radiation-induced ROS by way of the detoxifying action of antioxidant enzymes (28,29). Our study showed more intracellular ROS in cells transfected with the PrxI silencing vector than wild-type cells after hydrogen peroxide treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have shown that overexpression of Prx I increases cellular resistance to oxidative stress (25)(26)(27). Radiation sensitivity might rely on the cells' ability to manage radiation-induced ROS by way of the detoxifying action of antioxidant enzymes (28,29). Our study showed more intracellular ROS in cells transfected with the PrxI silencing vector than wild-type cells after hydrogen peroxide treatment.…”
Section: Discussionmentioning
confidence: 57%
“…The imbalance between oxidant/antioxidants is leading to an excessive production of oxygen metabolites, which creates an oxidative stress (Ho et al, 1998). Antioxidants have the capacity to reduce harmful effects of radiation on normal tissues (Okunieff et al, 2008). Antioxidants supplements reduce the treatment-related adverse effects, which occur during radiation therapy by overcome the oxidative damage to normal cells (Lawenda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Otsuka et al (6) demonstrated that exposure of mice to 0.5 Gy at a dose rate of 1.2 mGy/h for 23 days increased the gene expression of catalase and MnSOD by a factor of 2.5, while at higher doses of 1.0 and 1.3 Gy at a similar dose rate, gene expression either increased by only 1.4 or was not significantly different from non-irradiated controls, respectively. The nucleus, cell membrane and mitochondria are considered sensitive targets for the reduction or prevention of radiation damage by antioxidants (7). One of the most studied effects of ionizing radiation is DNA damage.…”
Section: Introductionmentioning
confidence: 99%